Degré et intensification : essai de typologie - Lucile Bordet; Denis Jamet (Anglophonia)
Existing typologies of degree and intensification processes all seem to overlook some aspects of the issue under scrutiny. They all focus on syntactic, semantic or morphosyntactic criteria leaving aside the phonological, lexical or stylistic dimensions of degree and intensification processes. We will first give our definitions of the terms “degree” and “intensification”, then we will present and discuss the existing typologies, which will lead us to present our own typology bearing in mind that the various processes often overlap.